Pengaruh Model Problem Based Learning berbantuan Mind Mapping terhadap Kemampuan Pemecahan Masalah Siswa - Imelda Wiguna; Arjudin Arjudin; Nurul Hikmah; Baidowi Baidowi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
The purpose of this study was to determine the effect of a mind mapping-assisted problem-based learning model on the problem-solving abilities of class IX students at SMP Negeri 1 Gunungsari in the 2020/2021 school year. This type of research is a pre-experimental research using a one group pretest-posttest design. The population in this study were all grade IX students. While the sample in this study is class IX E with random cluster sampling. Based on the results of the pretest and posttest data analysis in the experimental class, it can be seen that the students' mathematical problem solving ability has increased by an average of 27%. Meanwhile, the results of the pretest and posttest data analysis in the control class increased by an average of 9%. Based on the results of hypothesis testing, it is obtained that the value of ttable with a significant level = 5% and dk = 12 from the t-distribution list obtained ttable of 1.78 and tcount of 5.40 which means tcount > ttable, then H0 is rejected so H1 is accepted. This means that there is an effect of the problem-based learning model with the aid of mind mapping on the problem-solving abilities of class IX students at SMP Negeri 1 Gunungsari for the 2020/2021 academic year.